Dual-Purpose Sorghum: A Targeted Sustainable Crop-Livestock Intervention for the Smallholder Subsistence Farming Communities of Adilabad, India - Anbazhagan, Krithika; Voorhaar, Marijn; Kholová, Jana; Chadalavada, Keerthi; Choudhary, Sunita; Mallayee, Srikanth; Kaliamoorthy, Sivasakthi; Garin, Vincent; Baddam, Rekha; Rao, Kumra Vittal; Nedumaran, Swamikannu; Selvaraj, Aravazhi (Frontiers in Sustainable Food Systems, 2022)
Sorghum plays an important role in the mixed crop–livestock system of tribal farming communities in Adilabad District, a high climate risk-prone region in India. Currently, the local seed system is limited to landraces and hybrids that are primarily used for domestic grain and fodder purposes. This study aimed to understand the farmers’ needs and context, and use this knowledge to deliver relevant, adoptable climate-smart sorghum crop technologies through farmer-participatory approaches (FPAs). We conducted an ex-ante survey with 103 farmer households to understand their preferences and constraints concerning sorghum, their staple food-crop. Farmers expressed taste as the most important characteristic, followed by stover yield, grain yield, drought adaptation, and pest resistance. They identified fodder deficit, loss of seed purity in landraces, and lack of diverse sorghum seed options as critical constraints. Therefore, we chose dual-purpose, open-pollinated sorghum varieties suitable for postrainy/ rabi cultivation as the study site’s entry point. Accordingly, sixteen popular rabi sorghum varieties were tested at ICRISAT station (2017–18 and 2018–19) for agronomic performance in field conditions under a range of treatments (irrigation and fertilization). The standing crop was also scored by farmer representatives. Additionally, the detailed lysifield study elucidated the plant functions underlying the crop agronomic performance under water stress (plant water use and stay-green score) and an important trait of farmer’s interest (relation between stay-green score and in-vitro stover digestibility and relation between grain fat and protein content) The selected varieties– Phule Chitra, CSV22, M35-1 and preferred landrace (Sevata jonna)–were further tested with 21 farmers at Adilabad (2018–20) Participating farmers from both the trials and focus group discussions voiced their preference and willingness to adopt Phule Chitra and CSV22. This paper summarizes how system-relevant crop options were selected for subsistence farmers of Adilabad and deployed using participatory approaches. While varieties are developed for wider adoption, farmers adopt only those suitable for their farm, household, and accessible market. Therefore, we strongly advocate FPA for developing and delivering farmer relevant crop technologies as a vehicle to systematically break crop adoption barriers and create a positive impact on household diets, well-being, and livelihoods, especially for smallholder subsistence farmers.